Multiscale synchrotron scattering studies of the temperature-dependent changes in the structure and deformation response of a thermoplastic polyurethane elastomer - Sui, T; Salvati, E; Zhang, H; Dolbnya, I; Korsunsky, A (Elsevier, 2019)
The distinct molecular architecture and thermomechanical properties of polyurethane block copolymers make them suitable for applications ranging from textile fibers to temperature sensors. In the present study, differential scanning calorimetry (DSC) analysis and macroscopic stress relaxation measurements are used to identify the key internal processes occurring in the temperature ranges between −10 °C and 0 °C and between 60 °C and 70 °C. The underlying physical phenomena are elucidated by the small-angle X-ray scattering (SAXS) and wide-angle X-ray scattering (WAXS) study of synchrotron beams, allowing the exploration of the structure-property relationships as a function of temperature. In situ multiscale deformation analysis under uniaxial cyclic thermomechanical loading reveals a significant anomaly in the strain evolution at the nanoscale (assessed via SAXS) in the range between −10 °C and 0 °C owing to the ‘melting’ of the soft matrix. Furthermore, WAXS measurement of crystal strain within the hard regions reveals significant compressive residual strains arising from unloading at ∼60 °C, which are associated with the dynamic shape memory effect in polyurethane at these temperatures.